Improving Hazard Communication and Visibility Effectiveness in a Chemical Manufacturing Industry - HANIFAH HUSNA AHMAD ZAIDIE; Zuritah A. Kadir; Durraini Daud (Progress in Engineering Application and Technology, 2026)
The chemical manufacturing industry is fundamentally unsafe, since it handles and stores dangerous chemicals, yet it’s important to the development of the economy. Effective hazard communication remains a core component of ensuring employees recognize risks and apply safe working behaviors. Deficiencies in visibility, placement, and clarity of safety signage continue to limit the effectiveness of hazard communication materials in too many chemical-manufacturing environments. The present study assesses the effectiveness of hazard communication and the visibility effect on safety information in a chemical manufacturing industry. Specifically, it tries to assess the workers’ knowledge, attitudes, and practices concerning hazard communication; establish visibility-related problems in safety signage and warning displays; and put forward practical improvements that could be used to enhance worker awareness and safety response. A mixed-methods research design was adopted for this study. The research was conducted at Sumisaujana TCM Chemical Sdn. Bhd., Selangor, involving 52 operational workers from the Main Plant. Quantitative data were collected using structured questionnaires, while qualitative insights were obtained through interviews and workplace observations focusing on signage visibility, placement, and condition. Finally, the identified trends, gaps, and areas for further improvement were analyzed from the data. The results showed that the workforce has a high level of knowledge and understanding with regard to hazard communication, such as labels, hazard symbols, and safety data sheets. Some areas were, however, found to be lacking with respect to the provision, placement, and maintenance of safety signs, which could have impaired its effectiveness. Even though the effectiveness associated with hazard communication is high, improvement is strongly advocated. Based on the results obtained, this study recommends improvement in sign design and location as well as sign maintenance and visibility audits, hazard information updating, and greater worker feedback as means of improving hazard communication in the workplace in chemical manufacturing plants.